Minimally invasive trigeminal ablation in patients with refractory trigeminal neuralgia who are ineligible for intracranial intervention. (December 2019) - Tajali, Yasser; Ward, Max; Abraham, Mickey; Hillen, Machteld; Mahmoud, Omar; Herschman, Yehuda; Mammis, Antonios; Paskhover, Boris
Highlights: We present an endoscopic approach to trigeminal nerve ablation in poor surgical candidates. All patients experienced complete pain relief post-operatively despite prior treatment failures. Pain relief is immediately assessable post-operatively. The procedure is short and safe in patients with multiple medical comorbidities. Abstract: We describe the use of minimally invasive trigeminal ablation, an endoscopic ablative technique to treat trigeminal neuralgia in patients who are traditionally poor surgical candidates. We present 4 patients who presented with refractory unilateral trigeminal neuralgia. Three of the patients had previously failed stereotactic radiosurgery and three of them have multiple sclerosis. Due either to lack of neurovascular compression, minimally invasive trigeminal ablation was offered. Intraoperatively, an incision is made along the buccal mucosa or mid-brow and the tissue is endoscopically dissected in a plane towards the symptomatic nerve. Once isolated, the epineurium is partially ablated with thermocautery and the tissue surrounding the nerve is decompressed. All patients reported resolution of their pain post-operatively and were pain free at last follow up. Two patients had mild hypesthesia over the ablated nerve territory. Minimally invasive trigeminal ablation is a safe and effective technique for symptomatic control of trigeminal neuralgia. The efficacy, low risk, and relative ease of the procedure makes it ideal for use in patients who are refractory to medical management and have no neurovascular compression, are unable to tolerate traditional surgery or have failed other therapies.